Durvalumab after concurrent chemotherapy and high-dose radiotherapy for locally advanced non-small cell lung cancer. (1st January 2021) - Landman, Yosef; Jacobi, Oded; Kurman, Noga; Yariv, Orly; Peretz, Idit; Rotem, Ofer; Dudnik, Elizabeth; Zer, Alona; Allen, Aaron M.
ABSTRACT: The standard of care for stage III non-small cell lung cancer (NSCLC) is chemoradiotherapy (CRT) followed by durvalumab. Although doses higher than 66 Gy are standard in our center, they were used in only 6.9% of patients in the PACIFIC trial. We report our experience with durvalumab after high-dose radiotherapy. The database of a tertiary hospital for patients with stage III NSCLC who were treated with CRT and adjuvant durvalumab was evaluated. Progression-free survival (PFS), overall survival (OS), and local-regional failure (LRF) were measured from the administration of durvalumab. Thirty-nine patients were included. All were treated with intensity-modulated radiation (mean dose 69.9 Gy); Median follow-up time was 20.4 months (range 1–35.4). At 12 months, PFS was 49%, OS 79%, and LRF 14%. Intrathoracic failure at first progression was demonstrated in 8 (21%) patients. Adverse events requiring corticosteroids occurred in 10(25.6%) patients: pneumonitis – 6 (15.4%), hepatitis – 2 (5.1%), and arthralgia and pericarditis – 1 (2.6%). One patient (2.6%) died of pneumonitis. The occurrence of pneumonitis was significantly associated with lung V5 (55% vs. 42%, p = .04) and V20 (28% vs. 19%, p = .01) and mean lung dose (14.8 Gy vs.11.6 Gy, p = .05). The similar 12-month PFS and OS rates of our cohort and the PACIFIC trial support the use of high-dose radiotherapy in patients with stage III NSCLC. Treatment-related mortality was similar to the PACIFIC results. The intrathoracic failure rate in our cohort was lower than that reported from the PACIFIC trial, suggesting that radiation dose escalation may improve local control.